Villagers are not affraid to die : qualitative study of community cohesion on pictorial warning on cigarette packaging with Grounded Theory approach in Yogyakarta - Dhiya Urrahman; Fatwa Sari Tetra Dewi; Fuad Hamsyah (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
PurposeThe purpose of this study was to explore community's coping againts pictorial health warning on cigarettes packaging.MethodA quaitative study was conducted involving in-depth interviews and focus group discussions (FGD) on the subject who were selected purposively with a maximum variation technique in the rural of Sambirejo, Prambanan sub- district, Sleman, YogyakartaResultsThis study found perceptions, beliefs, coping, adaptation period, and smoking behavior after seeing pictorial warnings on cigarette packaging. Perception of the community consists of knowledge, feelings (disgust, horror, fear, sad and ordinary), and comments on pictorial warnings on cigarette packs. Beliefs include sure, hesitant and unsure. Beliefs are influenced by perception and could determine the coping. Coping appears that the attempt to avoid a pictorial warnings on cigarette packs. The feeling and coping were influenced by the length of exposure to pictorial warnings (period of adaptation). Pictorial health warning made non-smokers did not want to smoke, and brought up the intention to quit smoking in smokers.ConclusionCoping influenced by perceptions, beliefs, period of adaptation to pictorial health warnings; the period of adaptation changed feelings and coping previously to the pictorial health warning; pictorial health warning on cigarette packs made non-smokers increasingly want to smoke. Images have a visual power in health hazard warnings. Use of more varied images needs to be done periodically.